2023
DOI: 10.3389/fcell.2023.1116424
|View full text |Cite
|
Sign up to set email alerts
|

The KDM5B and KDM1A lysine demethylases cooperate in regulating androgen receptor expression and signalling in prostate cancer

Abstract: Histone H3 lysine 4 (H3K4) methylation is key epigenetic mark associated with active transcription and is a substrate for the KDM1A/LSD1 and KDM5B/JARID1B lysine demethylases. Increased expression of KDM1A and KDM5B is implicated in many cancer types, including prostate cancer (PCa). Both KDM1A and KDM5B interact with AR and promote androgen regulated gene expression. For this reason, there is great interested in the development of new therapies targeting KDM1A and KDM5B, particularly in the context of castrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Although the synergistic effects of LSD1 inhibitors and other protein inhibitors, such as BRD4 and NAE, have been confirmed, there have not been multitarget drugs based on LSD1 and other proteins. Here, we summarize the combined application of LSD1 inhibitors with other targeted drugs, , hoping to provide theoretical guidance for the development of multitarget drugs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the synergistic effects of LSD1 inhibitors and other protein inhibitors, such as BRD4 and NAE, have been confirmed, there have not been multitarget drugs based on LSD1 and other proteins. Here, we summarize the combined application of LSD1 inhibitors with other targeted drugs, , hoping to provide theoretical guidance for the development of multitarget drugs.…”
Section: Discussionmentioning
confidence: 99%
“…111 Recently, Metzler et al reported that in PCa, LSD1, and KDM5B exhibited synergistic effects in regulating AR expression and signaling. 97 Following this, they assessed the impact of CPI-455 (a KDM5B inhibitor) alone or in combination with Namoline (an LSD1 inhibitor) on the proliferation and invasion of AR-driven PCa cell lines (Table 2). The results showed that CPI-455 reduced the androgeninduced expression of AR target genes KLK3/PSA and downregulated several genes related to cancer pathways such as Hippo, WNT, and PI3K/AKT.…”
Section: Combination Of Lsd1 Inhibitor and Brd4mentioning
confidence: 99%
See 1 more Smart Citation
“…Development and progression of CRPC are an intricate process involving the alterations of many molecular pathways, 3 of which a major component is the PI3K/AKT signaling pathway. 4,5 Although there are therapies in clinical trials to treat CRPC (e.g., docetaxel and enzalutamide), resistance to these therapies occurs in most patients, which may lead to malignant progression. Therefore, novel, and effective treatment strategies are needed to improve the therapeutic potential against CRPC.…”
Section: Introductionmentioning
confidence: 99%
“…Although androgen deprivation therapy (ADT) is the first‐line treatment to primary PCa, relapse is often observed in most PCa patients who ultimately develop castration‐resistant prostate cancer (CRPC). Development and progression of CRPC are an intricate process involving the alterations of many molecular pathways, 3 of which a major component is the PI3K/AKT signaling pathway 4,5 . Although there are therapies in clinical trials to treat CRPC (e.g., docetaxel and enzalutamide), resistance to these therapies occurs in most patients, which may lead to malignant progression.…”
Section: Introductionmentioning
confidence: 99%